Modelling and Control of Liquid Level System - Yaacob, Marizan (2001)
Control system modelling is difficult and delicate process. In most cases, the model cannot be obtained directly from the plant due to the complexity of the system components or the internal structure of the system is not sufficiently understood to allow analytical formulation of equations. On the other hand, the model can be proposed by investigating the dynamic characteristics of the system experimentally. In this study, a model of a liquid level system is to be derived. The experimental data was obtained by applying a step input and measuring the output response of the system. A transfer function was estimated by using curve fitting technique. This estimated model has been refined by tuning the parameters e.g. gain, time constant, natural frequency and damping ratio. Control design has also been carried out based on the model obtained through simulation. PD control has found to be superior compared to PID. The same parameter settings of the controllers was applied to the real plant and performance of the system under PD control was satisfactory. This also proved that the model derived was a good estimate of the real plant and it can be used for further control design.